Action Mechanism for 3?-Hydroxykaurenoic Acid and 4,4-Dimethylanthracene-1,9,10(4h)-Trione on Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Saavedra-Flores, A (Allen Press Inc., 2015)
The mechanism of action of the diterpenoid 3β-hydroxykaurenoic acid and the anthraquinone 4,4-dimethylanthracene-1,9,10(4H)-trione on the phytopathogenic fungus Botrytis cinerea was studied. The effect of both compounds on the respiratory process and on the membrane integrity of B. cinerea was evaluated. The results showed that 3β-hydroxykaurenoic acid inhibited the growth of this fungus by disrupting the plasmatic membrane. This compound also partially affected oxygen consumption of B. cinerea germinating conidia. On the other hand 4,4-dimethylanthracene-1,9,10(4H)-trione did not produce membrane disruption of B. cinerea. The effect of this compound on mycelial growth was notably increased by the presence of an inhibitor of the cyanide-resistant respiration pathway. It also was shown that the anthraquinone inhibited oxygen consumption by about 80%; therefore this compound would act as a potent inhibitor of the cytochrome pathway of the respiratory chain to exert its antifungal effect. © 2015 by The Mycological Society of America, Lawrence, KS 66044-8897.